Conserved Discrimination Against Misacylated tRNAs by Two Mesophilic Elongation Factor Tu Orthologs - Cathopoulis, Terry J. T. (2008)
Elongation Factor Tu (EF-Tu) binds and loads elongating aminoacyl-transfer RNAs (aa-tRNAs) onto the ribosome for protein biosynthesis. Many bacteria biosynthesize Gln-tRNA(Gln) and Asn-tRNA(Asn) by an indirect, two-step pathway that relies on the misacylated tRNAs Glu-tRNA(Gln) and Asp-tRNA(Asn) as essential intermediates. Previous thermodynamic and experimental analyses have demonstrated that Thermus thermophilus EF-Tu does not bind Asp-tRNA(Asn) and predicted a similar discriminatory response against Glu-tRNA(Gln) [Asahara, H. and Uhlenbeck, O., (2005), Biochemistry 46, 6194–6200 and Roy, H. et al. (2007) Nucleic Acids Research 35, 3420–3430]. By discriminating against these misacylated tRNAS, EF-Tu plays a direct role in preventing misincorporation of aspartate and glutamate into proteins at asparagine and glutamine codons. Here we report the characterization of two different mesophilic EF-Tu orthologs, one from Escherichia coli, a bacterium that does not utilize either Glu-tRNA(Gln) or Asp-tRNA(Asn), and the second from Helicobacter pylori, an organism in which both misacylated tRNAs are essential. Both EF-Tu orthologs discriminate against these misacylated tRNAs, confirming the prediction that Glu-tRNA(Gln), like Asp-tRNA(Asn), will not form a complex with EF-Tu. These results also demonstrate that the capacity of EF-Tu to discriminate against both of these aminoacyl-tRNAs is conserved even in bacteria like E. coli that do not generate either misacylated tRNA.